Social Media Stimuli and Impulsive Buying: The Mediating Role of FOMO and Generational Differences - Tinjung Desy Nursanti; Yordan Gustiawan (Indonesia Banking School, 2026)
The massive adoption of social media has accelerated spontaneous consumption behaviors among digital users. This study aims to analyze the dual effect of social media platforms and contents on impulsive buying behavior of active users in Indonesia, by examining Fear of Missing Out (FOMO) as a psychological mediator and generational differences as a moderating factor. Quantitative data were obtained from a purposive sample of 208 active social media users who have made impulsive purchases, based on the Stimulus–Organism–Response (SOR) framework. The hypothesis was tested using the Partial Least Square-Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4.0 software. Empirical results reveal that social media platforms (β = 0.401) and digital content (β = 0.518) have a favorable and significant impact on FOMO which further enhances consumers’ want for unplanned purchases (β= 0.476). The interaction moderation analysis (β = 0.516) also found that age variations considerably increase the relationship between FOMO and impulse purchase, with younger groups showing stronger psychological reactions. These findings contribute to the research on internet consumer behavior regarding psychological dynamics and age cohorts and provide generational targeting-based marketing techniques for digital firms.